2022
DOI: 10.15583/jpchrom.2022.009
|View full text |Cite
|
Sign up to set email alerts
|

Photostabilities of Amlodipine OD Tablets in Different Dosage Forms

Abstract: Amlodipine is a dihydropyridine drug that is used to lower high blood pressure. In this study, the photostabilities of orally disintegrating (OD) amlodipine tablets, both original and generic versions, and their powdered and suspended forms were evaluated. The concentration of the active pharmaceutical ingredient (API) was monitored by high-performance liquid chromatography (HPLC), revealing that residual amounts of API in powders and suspensions significantly decreased after ultraviolet light (UV) irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In the MS/MS spectrum, one fragment ion ( m / z 354.00) was detected ( Figure 6 B) and seemed to be generated by the elimination of an ethyl group ( Figure 6 C). It is indicated that the oxidation of a dihydropyridine ring resulted in the decrease in its polarity because FL photoproduct 1 eluted faster than FL as shown in Figure 2 , the same as our previous report [ 3 ]. In addition, a pyridine derivative showed no characteristic absorption among 300 to 400 nm, which differs from FL as shown in Figure 3 B.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the MS/MS spectrum, one fragment ion ( m / z 354.00) was detected ( Figure 6 B) and seemed to be generated by the elimination of an ethyl group ( Figure 6 C). It is indicated that the oxidation of a dihydropyridine ring resulted in the decrease in its polarity because FL photoproduct 1 eluted faster than FL as shown in Figure 2 , the same as our previous report [ 3 ]. In addition, a pyridine derivative showed no characteristic absorption among 300 to 400 nm, which differs from FL as shown in Figure 3 B.…”
Section: Resultssupporting
confidence: 86%
“…In a clinical situation, there are several cases where tablets are crushed and packaged followed by storage in the houses of patients. Our previous reports also showed that long-term storage (for up to 90 days) of crushed amlodipine oral disintegration tablets in the package near the window of a house, where it is exposed to sunlight irradiation, resulted in a decrease in their APIs [ 3 ]. The decrease in APIs means the weakening of the beneficial effect of a medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The change of the dosage form of two original amlodipine orally disintegrating (OD) tablets, Amlodin ® OD tablets and Norvasc ® OD tablets, induced the decrease of their photostability as shown in Table 2. Residual amounts of API significantly decreased compared to the control samples when both tablets were UV-irradiated after crushing or suspending [58]. Furthermore, these OD tablets and their powders were packaged and stored in a house and a pharmacy for up to 90 days for the purpose of evaluating their photodegradability.…”
Section: The Photostability Evaluation Of Several Medicines and Their...mentioning
confidence: 99%
“…In particular, an appropriate choice of stationary phase is quite important [8][9][10][11][12]. Octadecylsilica (ODS) is the most popular stationary phase in reversed-phase (RP) LC owing to its good separation performance for various complex sample mixtures [13][14][15][16][17][18][19]. The chemical structure of ODS comprises chemically-bonded octadecyl groups on the surface of silicagel particles.…”
Section: Introductionmentioning
confidence: 99%